PENINGKATAN LOMPAT TINGGI MENGGUNAKAN PENDEKATAN BERMAIN DI SMPN 01 KECAMATAN PENGKADAN - Junaidi, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of the study is to determine the level of teaching high jump with approach play in class VIII Junior High School 01 District Pengkadan. Forms of research is classroom action research . Subjects in the study of this class action is a class VIII student of SMPN 01 District Pengkadan Kapuas Hulu as many as 23 students, consisting of 12 sons and 11 daughters. Based on the results obtained in the first cycle of students who pass amounted to 7 students or 30.4 %, while the students who have not completed totaling 16 students or 69.6 %. To repair the high jump next stage is to conduct research using the approach of the second cycle of the game and the results obtained completeness of 100% or all students completed with 23 students and a number of unresolved at 0% or amounted to 0 or does not exist. Keywords: High Jump, Playing, Learning Outcomes